OVERVIEW: PROCESS PARAMETERS FORHYDROTHERMAL SYNTHESIS OF HYDROXYAPATITE - M., Fatimah; A., Shaaban; S., Seliman, (Journal of Advanced Manufacturing Technology (JAMT), 2014)
Hydroxyapatite is the most interesting subject to be studied especially for its suitability as an alternative to human bone and has become a biomaterial ceramic that resembles the composition of our bone minerals and are able to respond biologically. The preferred synthesis method is Hydrothermal which produces HA nano-sized particles with customized morphology and desired crystallinity by varying the process parameters. The morphology and the crystallinity of the synthetic powder particles influence the mechanical properties of manufactured products. This paper reviews the variable factors in hydrothermal method which includes type and concentration of starting material, temperature, time, pressure and pH conditions and presence of additives.